Article Commentary: Drug–Drug Interactions in HIV Therapy: Is it All Clear?. Issue 5 (July 2013) - Burger, David; Back, David
Drug–drug interactions in HIV therapy have been known to the clinic from earliest days of HIV treatment. Hundreds of well-designed pharmacokinetic studies have been performed in either HIV-infected patients or, mostly, in healthy volunteers. Case reports generally are graded lower in terms of evidence-based medicine but sometimes provide valuable information. In this issue of Antiviral Therapy a case of virological failure on an atazanavir-containing regimen was explained by an interaction with charcoal that was used as self-medication for diarrhoea. Clinicians are invited to continue submitting well-documented case reports to increase knowledge on drug–drug interactions in HIV therapy even further.